2021
DOI: 10.3892/mmr.2021.11904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mtDNA depletion from C6 glioma cells and characteristics of the generated C6ρ0 cells

Abstract: Malignant tumors of the central nervous system (CNS) are among the types of cancer with the poorest prognosis and glioma is the commonest primary CNS tumor. A mitochondrial DNA (mtDNA)-depleted cell line C6ρ0 was generated from C6 glioma cells after long-term exposure to ethidium bromide and 2' ,3'-dideoxycytidine in order to determine the effect of mtDNA damage on cell proliferation and pathological changes in glioma cells. Single cell clones were isolated and identified after 42 days of incubation. Repopulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…These results were further confirmed using rho zero (ρ0) C6 cells as control, which were generated by treatment of ethidium bromide (EB) and 2′,3′-dideoxycytidine (ddC) (fig. S1, I and J) ( 20 ). It has been reported that mutations in mtProteins generally impair the assembly or stability of OXPHOS complexes ( 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were further confirmed using rho zero (ρ0) C6 cells as control, which were generated by treatment of ethidium bromide (EB) and 2′,3′-dideoxycytidine (ddC) (fig. S1, I and J) ( 20 ). It has been reported that mutations in mtProteins generally impair the assembly or stability of OXPHOS complexes ( 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cell culture, nucleofection, and sorting C6 cells (American Type Culture Collection, CCL-107) were cultured in Dulbecco's modified Eagle's medium (DMEM) (A1896701, Gibco) supplemented with 10% fetal bovine serum (FBS) (10099141C, Gibco) at 37°C with 5% CO 2 and were detected without mycoplasma contamination by PCR test. C6 ρ0 cells were generated using EB and ddC treatment as previously described (20). Briefly, wild-type C6 cells were exposed to 10 μM EB (E8751, Sigma-Aldrich) and 16 μM ddC (D5782, Sigma-Aldrich) in DMEM supplemented with uridine (50 μg/ml; U3003, Sigma) and pyruvate (0.1 mg/ml; 11360070, Gibco), with a daily change of the culture medium.…”
Section: Plasmids Constructionmentioning
confidence: 99%
“…Various causes of mitochondrial dysfunction in cancer cells are known, such as mtDNA mutations and enzyme defects [ 13 , 14 ]. Mitochondrial dysfunction in cancer cells can be induced by gene editing or by depleting mtDNA using chemicals [ 28 , 29 , 30 ]. In a previous study, we generated mitochondria dysfunctional (ρ 0 ) cells, Hep3B/ρ 0 cells, by mtDNA depletion and showed that these Hep3B/ρ 0 cells exhibited an epithelial-mesenchymal transition, a malignant phenotype.…”
Section: Introductionmentioning
confidence: 99%